England's Rare Mosses and Liverworts : Their History, Ecology, and Conservation - Porley, Ron D. (Book collections on Project MUSE., 2013)
This is the first book to cover England's rare and threatened mosses and liverworts, collectively known as bryophytes. As a group, they are the most ancient land plants and occupy a unique position in the colonization of the Earth by plant life. However, many are at risk from habitat loss, pollution, climate change, and other factors. Britain is one of the world's best bryologically recorded areas, yet its mosses and liverworts are not well known outside a small band of experts. This has meant that conservation action has tended to lag behind that of more charismatic groups such as birds an.